What does better peer review look like? Underlying principles and recommendations for better practice. Issue 2 (10th January 2019) - Allen, Heidi; Cury, Alexandra; Gaston, Thomas; Graf, Chris; Wakley, Hannah; Willis, Michael
Abstract : We conducted a literature review of best practice in peer review. Following this research, we identified five principles for better peer review: Content Integrity, Content Ethics, Fairness, Usefulness, and Timeliness. For each of these principles, we have developed a set of recommendations to improve peer review standards. In this article, we describe the role of peer review and how our five principles support that goal. This article is intended to continue the conversation about improving peer review standards and provide guidance to journal teams looking to improve their standards. It is accompanied by a detailed checklist, which could be used by journal teams to assess their current peer review standards.